A residência secundária e uso do espaço público no litoral oriental potiguar - Silva, Kelson de Oliveira (2010)
Considering that tourism tends to reproduce itself privatizing the areas where it installs, the secondary residence has been an urban element responsible for the private appropriation of the public spaces of coastal of Nísia Floresta. The private appropriation of these accesses, for secondary residences, constitute in an issue-problem of the research. The principal goal is to analyze the relationship of the consumers/users of secondary residences with the public space; and, specifically, identify how the government has been acting and manifesting itself about the occupation of the coastal of Nísia Floresta; as also to verify how the secondary residence has been appropriating privately of the public access of the coastal. On account of the scarce literature about secondary residences and the importance of the public access to beaches for the inhabitant, the present work aims to contribute to the discussion of this theme. The secondary residences in Rio Grande do Norte began in the late nineteenth century, becoming more common in the 90s, when the coast south of Natal is appropriated from local vacationers. In 2000, foreign investment began to be applied in real state and tourism, producing closed developments, served in leisure infrastructure, trade, and hospitality, mainly to external demands. The methodology included a bibliographic survey, data collection and in lócus observation. Applied questionnaires and interviews were performed with consumers/users of the secondary residences, permanent residents and government, respectively. To the legal grounding, taken as a reference the article. 10, of the law 7.661/88 to establish that the beaches are goods of common use . Considering the conclusive analysis of the research, can be said that the right of free access and use of the beach is committed for the benefit of the consumers/users of secondary residences, due to the negligence and omission of the government